2022
DOI: 10.1186/s12870-022-03810-7
|View full text |Cite|
|
Sign up to set email alerts
|

Hormone biosynthesis and metabolism members of 2OGD superfamily are involved in berry development and respond to MeJA and ABA treatment of Vitis vinifera L

Abstract: Background Hormones play an indispensable role during fruit ripening, nine clades in 2-oxoglutarate-dependent dioxygenase (2OGD) superfamily are responsible for the hormone biosynthesis and metabolism, but less information is known about them. Results A total of 163 Vv2OGD superfamily members were identified from grape genome, which were mainly expanded by local (tandem and proximal) duplication. Phylogenetic analysis of 2OGD members in grape and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Previous research has revealed that the JA/SA signaling pathways jointly downregulate genes associated with gibberellin, redirecting growth resources towards defense (Zhang et al, 2020) [50]. In V. vinifera, the transcript levels of VvGA2ox1a, VvGA2ox10 and VvGA2ox11 were upregulated significantly after MeJA treatment (Gao et al, 2022) [51]. Similarly, CaGA2ox1 was induced and upregulated expression by salicylic acid treatment in pepper (Lee et al, 2012) [52].…”
Section: Discussionmentioning
confidence: 93%
“…Previous research has revealed that the JA/SA signaling pathways jointly downregulate genes associated with gibberellin, redirecting growth resources towards defense (Zhang et al, 2020) [50]. In V. vinifera, the transcript levels of VvGA2ox1a, VvGA2ox10 and VvGA2ox11 were upregulated significantly after MeJA treatment (Gao et al, 2022) [51]. Similarly, CaGA2ox1 was induced and upregulated expression by salicylic acid treatment in pepper (Lee et al, 2012) [52].…”
Section: Discussionmentioning
confidence: 93%
“…According to prior research, EBR could significantly increase grape berry size and sugar content as well as improved grape color and flavor formation ( Li et al., 2022 ; Lv et al., 2022a ). Similarly, JA could also contribute to berry expansion, sugar accumulation, and anthocyanins formation ( Yu et al., 2020 ; Gao et al., 2022 ; Wang et al., 2022 ). In agreement with the results of previous research ( Li et al., 2022 ), this study further verified the results that EBR and JA also promoted the biochemical properties of ‘Ruidu Hongyu’ grapevine.…”
Section: Discussionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], an error was identified in the presentation of the two authors. Gao Yingying and Wang Xiaochen should be presented as Yingying Gao and Xiaochen Wang.…”
mentioning
confidence: 99%